Transient Receptor Potential channels (TRP) in GtoPdb v.2022.1. (2022) - Blair, Nathaniel T.; Carvacho, Ingrid; Clapham, Dipayan Chaudhuri David E.; DeCaen, Paul; Delling, Markus; Doerner, Julia F.; Fan, Lu; Grimm, Christian M.; Ha, Kotdaji; Julius, Sven E. Jordt David; Kahle, Kristopher T; Liu, Boyi; et al.
No abstract available